Performance evaluation of WPT based islanding detection for grid-connected PV systems. (June 2016) - Pinto, Smitha Joyce; Panda, Gayadhar
Highlights: Islanding detection of grid connected PV system. Accurate and fast detection of islanding situation and power quality disturbances based on WPT. Comparative performance analysis of WT and WPT based detection. Abstract: Recent developments in power electronics technology have emerged towards the generation of electrical power from the renewable energy sources. Among renewable energy sources, solar energy has garnered more importance because of less maintenance and environmental friendly. In grid connected mode, distributed power generation system (DPGS) requires reliable islanding detection technique to find the electrical grid status and operate the grid connected inverter effectively. This paper investigates a comparative performance analysis of wavelet transform (WT) and wavelet packet transform (WPT) based detection in a three-phase grid connected PV inverter system under various power quality disturbances and islanding situation. The WT and WPT coefficients are determined by applying db4 wavelet basis functions, which are obtained optimally for analyzing perturbations that occur in grid connected PV system. The wavelet transform produces large errors due to spectral leakages in frequency bands. On the other hand, WPT provides uniform frequency subband with better time frequency resolution over WT. Finally, the feasibility of proposed WPT based islanding detection method is verified by simulating the system in MATLAB/SIMULINK environment. The simulated results demonstrate the better performance of WPT over WT technique and proved as an accurate, fast and reliable detection technique.